Active surveillance identified a neglected burden of macular cases of Post Kala-azar Dermal Leishmaniasis in West Bengal. - Ritika Sengupta; Surya Jyati Chaudhuri; Srija Moulik; Manab Kumar Ghosh; Bibhuti Saha; Nilay Kanti Das; Mitali Chatterjee (Public Library of Science (PLoS), 2019)
Background Post Kala-azar Dermal Leishmaniasis (PKDL) develops in patients apparently cured of Visceral Leishmaniasis (VL), and is the strongest contender for being the disease reservoir. Therefore, existence of a few cases is sufficient to trigger an epidemic of VL in a given community, emphasizing the need for its active detection and in turn ensuring success of the current elimination program. This study explored the impact of active surveillance on the demographic profile of PKDL patients in West Bengal. Methodology/principal findings Patients with PKDL were recruited through passive (2003-date, n = 100) and active surveillance (2015-date, n = 202), the former from outpatient departments of dermatology in medical colleges in West Bengal and the latter through an active door-to-door survey in four VL hyper-endemic districts of West Bengal. Passive surveillance indicated a male preponderance and a predominance of polymorphic lesions, whereas active surveillance indicated absence of any gender bias and more importantly, macular PKDL constituted almost 50% of the population burden. In terms of polymorphic vs. macular PKDL, the former appeared at a later age, their disease duration was longer and had a higher parasite burden. In the polymorphic variant, the lesional distribution was asymmetrical, comprised of papules/nodules/macules that were present mainly in sun-exposed areas whereas in macular cases, the hypopigmented patches were diffusely present all over the body. Conclusions/significance Active surveillance unraveled a disease component whose demographic profile showed important differences with PKDL cases who sought treatment in government hospitals. Detection of a higher proportion of macular cases indicates that this variant is not an uncommon presentation as conventionally stated in text books, and should be studied in greater detail to ensure success of the ongoing Leishmaniasis elimination programme.